Canada : 2008 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
Canada has enjoyed high growth while adjusting smoothly to commodity price gains, currency appreciation, and, more recently, slowing U.S. demand. Monetary policy has appropriately shifted to guarding against increasing near-term downside risks. A sound fiscal framework policy has produced an enviably strong fiscal position that makes eliminating general government net debt feasible. The budgetary overperformance provides room for tax relief while maintaining small budget surpluses. To foster efficiency, the fiscal room should be used to reduce high marginal effective tax rates on capital, saving, and labor.